Development and implementation of an intraoral device for occlusal stability during sports performance: A case report - Silva, D.; Mendes, J.; de Azevedo e Castro, J.; Ferreira, D.; Moreira, A.; Pais Clemente, M.; Vasconcelos, M. (Dentistry Journal, 2018)
Introduction: Sports dentistry assumes a clinical relevance, not only in the prevention of orofacial trauma by the use of mouthguards, but also with the development of intraoral devices that aim to provide greater occlusal stability, as well as a greater balance in the level of certain structures of the cranio-cervical-mandibular complex. In this way, the dentistry can have an intervention action on sports performance. Objectives: The objective of this research was to verify the existence of a correlation between occlusal stability and an eventual balance of some facial structures during sports performance using a specially developed Occlusal Stability Sports Performance Device. Methodology: An individualized mandibular intraoral device was manufactured and evaluated on an athlete canoeing. Infrared thermography was the complementary diagnostic method used for this purpose. Results: Greater symmetry of certain regions of interest of the cranio-cervico-mandibular complex was observed with the implementation of the Occlusal Stability Sports Performance Device. These areas were the anterior temporal muscle, the masseter muscle and the temporomandibular joint. No asymmetry decrease was found in the anterior triangle region of the neck. Conclusion: The use of this type of intraoral devices may allow greater occlusal stability and consequent balance of anatomical structures constituting the cranio-cervical-mandibular complex. Infrared thermography is an effective diagnostic tool for studying the results of the intraoral device on the cranio-cervico-mandibular complex use during canoeing.